Candida species colonization in oral lichen planus: A meta-analysis - Rodriguez-Archilla, Alberto; Fernandez-Torralbo, Silvia (International Journal of Health Sciences, 2022)
Objective: Oral lichen planus (OLP) is a common chronic inflammatory disease that affects 1%–2% of the population. Candida species superinfection can aggravate the symptoms of OLP, especially of the erosive forms, and promote malignant transformation by producing carcinogenics as nitrosamines or acetaldehyde. On the other hand, antifungal treatment of Candida-infected OLPs improves the clinical symptoms of the disease. The objective of this study is to assess the possible influence of Candida species colonization in oral lichen planus. Methods: A search for studies on Candida and oral lichen planus was performed in the following databases: PubMed (MEDLINE, Cochrane Library), Web of Science (WoS), and Scopus. Data analysis: The estimated prevalence of Candida detection in OLP was calculated according to the DerSimonian and Laird random model. For dichotomous outcomes, the estimates of effects of an intervention were expressed as odds ratio (OR) using Mantel-Haenszel (M-H) method with 95% confidence intervals. Results: Twenty-four studies were included in this meta-analysis. The estimated prevalence of Candida species detection in oral lichen planus (OLP) lesions was 37.00% (95% CI: 30.52–43.72%). OLP patients were almost 2½ times more likely to be infected by Candida species compared to healthy controls (OR: 2.48, P < 0.001). Likewise, Candida species superinfection was more likely in erosive OLP forms (OR: 2.53, P < 0.001), and by non-albicans Candida species (OR: 2.33, P = 0.02). Conclusions: More than one-third of OLP lesions are infected by Candida species, modifying their biological behavior.